STABILITY ANALYSIS FOR EMBANKMENTS WITH GEOELECTRICITY - Teddy Wartono Sudinda (Jurnal Sains dan Teknologi Mitigasi Bencana, 2020)
The collapse of the embankment is a problem that needs attention to find the right solution, so that the risk can be minimized. The condition of the embankment is influenced by the strength of the soil layer of the embankment, groundwater flow in the embankment, the condition of the water level of the embankment and human activities around the embankment. Changes in the quality of soil density in the embankment can form cavity zones within the embankment which cause changes in groundwater flow patterns in the embankment. The degradation of the soil layer of the embankment can cause piping, overtopping which is the cause of erosion of the embankment body and disturbs the stability of the embankment. Therefore, to determine the condition of the embankment soil layer, research on the stability of the embankment has been carried out using the geoelectric method at the location of the embankment in the Cipancuh and Penjalin reservoirs, so that an image of the embankment soil layer is obtained to determine the cavity zones in the embankment, the flow pattern in the embankment soil layer. Keywords:  cavity zones, flow patterns, geoelectric methods, the stability of the embankment.